Evidence for detachment faulting on the NE Parnassos mountain front (Central Greece) - KRANIS, H. D.; PAPANIKOLAOU, D. I. (Bulletin of the Geological Society of Greece, 2001)
The Mt Parnassos NE front (central-eastern mainland Greece) may owe its existence to the occurrence of a detachment fault, which is a re-used alpine overthrust surface. Neotectonic graben formation and segmented fault systems can be linked to this detachment fault, the reactivation of which could be attributed to the propagation of the dynamics of the Anatolian Block into the Aegean territory. The detachment kinematics is also confirmed through the use of a new kinematic indicator, formerly used only in metamorphic rocks